AGROECOLOGICAL FEATURES OF CULTIVATION AND INFLUENCE OF SOWING RATES ON OAT YIELD - Mazurak І.; Tyrus М.; Lytvyn О.; Mazurak О. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
The article presents the results of field research on dark gray podzolized soil on the formation of oat grain yield depending on the sowing rate and agro-ecological features of growing oats in the conditions ща the Western Forest-Steppe of Ukraine. The film-coated oat variety Zakat was sown on April 2 to a depth of 3–4 cm with 15 cm between rows. The influence of the following sowing rates, namely 3.0; 4.0; 5.0; 6.0 million/ha on oat yield was studied. The rate of application of mineral fertilizers was N120Р30K60. Granstar herbicide (25 g/ha) was used during the crop treatment, along with Trend adhesive (200 g/ha). They were introduced in the tillering phase. Research has revealed that the size of the oat harvest directly depends on the number of seeds sown per hectare. A decrease in the sowing rate leads to a reduction in the yield of oats. The Zakat variety demonstrated the maximum grain yield during the entire studied period at the seed sowing rate of 6.0 million/ha, reaching 4.39 t/ha. The seeding rate of 5.0 million/ha showed a somewhat lower level of productivity – 4.34 tons/ha. At the seeding rate of 4.0 million/ha, the oat grain yield continued to decrease to 4.10 t/ha. The studies have shown that reducing the density of planting plants to 3.0 million/ha led to a decrease in the yield of the Zakat variety by 0.64 t/ha (3.75 t/ha). In this study, it was established that the weight of 1000 oat seeds had no effect on yield. At the seed sowing rate of 3.0 million/ha, the weight was the largest, i.e. 36 g. The plants were well lit, and provided with moisture, but the yield at this rate was the lowest. Oats at the seed sowing rate of 6.0 million/ha provided an optimal combination of panicle density and grain mass. There was also a difference in the protein content of oat seeds depending on the sowing rate. The data show that the Zakat variety has the lowest protein content, i.e. 11.90 % at the sowing rate of 6.0 million/ha. And the highest grain quality index of oats of the Zakat variety was obtained at a plant stand density of 3.0 million/ha at the level of 12.32 %. Oat plants with lower seeding rates are better lit and have a larger feeding area during the growing season.